Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan pada suatu Layanan Purna Jual Motor Honda - muhammad hafiduddin; Hafid Syarif Hidayatulloh; Firdaus Hendri Kurniawan; Muhamad Rafi Sigit Widodo; Wilson Chandra Teguh Pratama (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2023)
ABSTRACTService quality assessment has been widely used in after-sales service, especially in the motor vehicle and automotive industry. The purpose of this study is to determine the factors that affect customer satisfaction in the after-sales service of Honda motorcycles at AHAS Gombong dealer by utilizing the SERVQUAL approach. Several SERVQUAL dimensions such as physical evidence or direct evidence (tangibles), (reliability), (responsive), (assurance), and (emphaty) are analyzed simultaneously on customer satisfaction. Structural Equation Modeling (SEM) shows that among the five dimensions of SERVQUAL, reliability and empathy are found to have a significant relationship with Honda motorcycle customer satisfaction in Gombong. Interestingly, (tangibles), (responsive), and (assurance) were found to have no significant relationship with satisfaction. Dealers must provide good service quality to meet customer expectations and achieve customer satisfaction, which in turn builds customer trust in the company. With this, customer loyalty can be achieved by the company which can also increase company profits and competitive advantage.Keywords : Tangibles, reliability, responsive, assurance, empathy